Evaluation of Electromyographic studies of masticatory muscles in Children with Cerebral Palsy - O.E. Idiev (International Journal on Human-Computing Studies, 2021)
The authors detail a new method of EMG studies in children with cerebral paralysis. EMG provides benefits as a highly informative and reliable technique with the ability to visualize and determine the parameters of the investigated muscles electroexitability dental-jaw apparatus in the diagnosis of dental-jaw anomalies among children with a cerebral paralysis